Study on Natural Preservation of Kampung Naga in Environmental Character Education Efforts in Primary Schools - Nadiyah, Diyah; Ningrum, Rafika Cahya; Jamaludin, Ujang (Pelangi (e-Journal), 2024)
Environmental education in elementary schools is crucial in forming children's environmentally caring character. This study draws inspiration from Kampung Naga, a traditional village in West Java, which shows natural sustainability and a relevant learning philosophy. Through an ethnographic approach, this research highlights the sustainable practices of the Kampung Naga community and applies them to learning at school. The results show that environmental care character education can be integrated through routine, spontaneous, exemplary and conditioning activities. This effort aims to form a generation that is not only academically intelligent, but also has awareness and commitment to environmental conservation. By combining local values, the principles of mutual cooperation, and community involvement, it is hoped that students can become active agents of change in preserving nature. Through the implementation of environmental care character education, it is hoped that it can create a society that is environmentally aware and contributes positively to ecosystem preservation.